Genetic Relatedness of 5-Year Isolates of Clostridioides difficile Polymerase Chain Reaction Ribotype 017 Strains in a Hospital - Jieun Kim; Mi-Ran Seo; Bongyoung Kim; Jinyeong Kim; Mi-Hyun Bae; Hyunjoo Pai (MDPI AG, 2021)
The objective of this study was to analyse the genetic relatedness of Clostridioides difficile polymerase chain reaction ribotype 017 (RT017) strains from patients with hospital-acquired C. difficile infection (HA-CDI) in a hospital with a high RT017 prevalence. From 2009 to 2013, 200 RT017 strains (26.8%) were collected from 745 HA-CDI patient isolates. They comprised 64 MLVA types, and 197 (98.5%) strains were genetically related to 5 clonal complexes (CCs). The largest cluster, CC-A, included 163 isolates of 40 MLVA types. CC-A accounted for 20% of RT017 strains in 2009 and sharply increased to 94.9% in 2010, 94% in 2011, 86.2% in 2012, and 73.5% in 2013. The other 4 CCs included 20 isolates with 7 MLVA types. The resistance rates of antimicrobials were as follows: clindamycin 100%, moxifloxacin 99%, rifaximin 88.5%, and vancomycin 1%. All isolates were susceptible to metronidazole and piperacillin/tazobactam. Comparing antibiotic resistance among CCs, the geometric mean of the minimum inhibitory concentrations of moxifloxacin, vancomycin, and piperacillin/tazobactam were significantly higher for CC-A isolates than for the other CCs. RT017 clones constantly evolved over the 5 years studied with regard to genetic relatedness. The levels of antibiotic resistance may contribute to the persistence of organisms in the institution.